Anti Money Laundering Mechanism: An Application of Principal-Agent Model for Pakistan - Khan, Sajawal
In this paper anti money laundering policy of the international financial regime is analyzed in principal agent model perspective. The strategy of the principal for formal agents is deliberated for global financial stability. This strategy encompasses incentive and dis-incentive for cooperation of formal agent. Formal agent by cooperating with principal may induce dis-incentive for informal agent. All the integrating stake holders make decision on the basis of comparison of present value of marginal cost of non-cooperation and present value of returns from cooperation. As the desired objective of the principal is to minimize transaction of money through informal channels therefore it has to include informal agents and clients in the strategy. The successful anti money laundering strategy can only be evolved by the cooperation of all the stakeholders.International Financial Regime, Principal Agent model and Money Laundering